Consumer communication when eating out of home: the role of technology. Issue 1 (20th August 2020) - Bray, Jeff; Hartwell, Heather; Appleton, Katherine; Price, Sarah
Abstract : Purpose: Despite growing demand, little product information is available when eating out. Information that is provided is often not well understood leading to a lack of consumer control and acting as a barrier to healthy food choices. The AIDA model which highlights the key stages of effective marketing communication (awareness, interest, desire and action) is applied. Information provided through technological solutions is examined to provide clear guidance on future use. Design/methodology/approach: Exploratory qualitative methods through four focused group discussions allowed consumers views to be probed in-depth and key themes to emerge through thematic analysis. Findings: In addition to the four key elements of the AIDA model, accessibility and relevance are found to be key constructs relevant to food information provision. Accessibility highlights the need for quick and clear data display, while relevance stresses how salient information is key to each consumer. Technological solutions may offer the most responsive, effective and trusted way to provide enhanced information. Practical implications: With increasing consumer demand for clear information, a competitive advantage can be gained through the provision of personalised enhanced dish information when eating out. Findings from this study highlight consumers' desire for online (app or website-based) platforms. Social implications: The provision of enhanced food information when eating out has clear public health implications and may influence choice leading to a reduction in non-communicable disease. Originality/value: This study evaluates consumers' perceptions to the provision of enhanced food information out of home providing novel insights and guidance for both managerial and societal impact.